LITERATURE REVIEW: EVALUASI KEBIJAKAN PROGRAM PENGELOLAAN SAMPAH BERBASIS 3R DI INDONESIA - Mei Tri Lutviana; Fasya Nabila Hidayat; Putri Sagita; Dita Nurliana; Anggara Setya Saputra (Jurnal Kebijakan Pemerintahan, 2025)
Abstract Indonesia faces serious challenges in waste management, Indonesia generates 68 million tons of waste annually, with only a 13.67% reduction rateöfar below the 30% target for 2025. This research evaluates the 3R (Reduce, Reuse, Recycle) policy using William N. Dunn's framework, examining six dimensions: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. A literature review analyzed 21 national and 19 international journals from Google Scholar. Findings reveal suboptimal 3R implementation with inconsistent regional achievements. Effectiveness is constrained by poor public awareness of waste sorting; efficiency suffers from inadequate operational funding; adequacy is limited by insufficient infrastructure and community engagement; equity shows uneven facility distribution; responsiveness varies with minimal community participation; and while policies are contextually appropriate, implementation overlooks local capacity. International comparisons demonstrate that successful 3R programs require behavioral change, robust regulations like Extended Producer Responsibility, continuous education, and strong multi-stakeholder collaboration. The research recommends adopting best practices from high-performing regions, establishing sustainable financing mechanisms, intensifying public awareness campaigns, and enhancing cross-sectoral coordination. These strategic interventions are essential for Indonesia to bridge the gap between current performance and national waste reduction targets, ultimately achieving more effective and equitable waste management nationwide. Keywords: Policy evaluation, Waste management, Indonesia.